Downstream effects: Impact of antibiotic pollution on an aquatic host–parasite interaction - Hannah G. Melchiorre; Stephanie O. Gutierrez; Dennis J. Minchella; J. Trevor Vannatta (Ecosphere, 2023)
Abstract The global increase in antibiotic use has led to contamination of freshwater environments. Despite the identified impacts of antibiotics on humans and wildlife, the effect of antibiotics on host–parasite life cycles in freshwater is relatively unexplored. In the current study, we utilize the trematode parasite Schistosoma mansoni, and its snail intermediate host, Biomphalaria glabrata, to investigate the influence of an ecologically relevant antibiotic concentration on the life history characteristics of both parasite and host. Our results demonstrate that antibiotics not only accelerate parasite development time, but also increase host reproduction and delay parasite‐induced host castration. Using a mathematical model, we suggest that life history alterations associated with antibiotics are likely to increase parasite transmission and disease burden. Our study suggests that antibiotic pollution could impact freshwater ecosystems by influencing host–parasite dynamics and potentially increase the burden of schistosomiasis in endemic regions.